J/[psi] and [psi]' total cross sections and formation times from data for charmonium suppression in pA collisions - He, Yong-Bin; Hüfner, Jörg; Kopeliovich, Boris Z. (Physics letters, 2000)
The recent data for E866 on the xF dependence for charmonium suppression in pA collisions at 800 GeV are analyzed using a time- and energy-dependent preformed charmonium absorption cross section. For charmonium-nucleon c.m. energy 10 GeV the initially produced premeson has an absorption cross section of σpr≃3 mb. At the same energy but for the developed charmonium states one deduces for the total cross sections σtotJ/ψN=(2.8±0.3) mb, σtotψ′N=(10.5±3.6) mb. The date are compatible with a formation time τ1/2=0.6 fm/c in the rest frame of the charmonium.